Determinants of Union Membership in 18 EU Countries : Evidence from Micro Data, 2002/03 - Claus Schnabel; Joachim Wagner (Institute for the Study of Labor (IZA), 2005)
Using representative individual-level data from the first round of the European Social Survey fielded in 2002/03, this paper provides an empirical analysis of unionization in 18 countries of the European Union. We show that union density varies considerably in Europe, ranging from 84 per cent in Denmark to 11 per cent in Portugal. Estimating identical models for each country, we find that individuals? probability of union membership is significantly affected by their personal characteristics, their attitudes and the characteristics of their workplace, whereas social factors seem to play a minor role. The presence of a union at the workplace and employees? attitudes concerning strong unions are the two variables with the most widespread effects on unionization.
Keywords: J51; 330; union membership; union density; Europe; Gewerkschaft; Mitgliedschaft; Schätzung; EU-Staaten